Kemampuan Berpikir Kreatif Siswa SMP melalui Model Problem Based Learning - Rika Siviani; Cut Morina Zubainur; Muhammad Subianto (Didaktik Matematika, 2018)
Creative thinking ability of students is still low and less attention in the implementation of the learning of mathematics. Some efforts are needed to foster creative thinking ability because of lack of creative thinking ability in the learning of mathematics. One of effort is applying Problem Based Learning (PBL) Model. The purpose of this research was (1) to describe the creative thinking ability of students during the learning process with PBL Model, and (2) to determine the increase of the creative thinking ability of students after implementation of PBL model. This research used mixed methods with concurrent triangulation strategy. Samples were selected by random sampling from all grade 8 students from one of junior high school at Banda Aceh, those were 28 students in class VIII-3. The instrument used to obtain data of the creative thinking ability of students after learning with PBL Model was test and observation. The instrument used to obtain data to determine the increase of the students creative thinking ability after learning with the PBL model were pretest and posttest. Test and observations were analyzed by using an assessment rubric of creative thinking abilities with descriptive qualitative method. The result of pretest and posttest were analyzed by statistical tests using t-test. The results showed that the students were creative in solving problems during the learning process with model of PBL. There was increasing creative thinking abilities of students after learning with PBL Model. The implication of this research indicates that creative thinking abilities of students increase through PBL model.